Socioeconomic gradients in the Westernization of diet in China over 20 years - Annie Green Howard; Samantha M. Attard; Amy H. Herring; Huijun Wang; Shufa Du; Penny Gordon-Larsen (SSM: Population Health, 2021)
Introduction: In low-middle income countries, urbanization leads to changes from traditional to Western diet, which are often accompanied by reductions in cardiometabolic health. Whether socioeconomic status buffers these urbanization-related diet changes over time is unknown. Objective: To examine whether the association between urbanization and a key indicator of Western diet, percent of calories from animal-source foods (1) varies depending on income and (2) whether this association changes over time. Materials and methods: We used data from nine waves of the longitudinal, population-based China Health and Nutrition Survey [n = 22,360 Chinese adults (1991–2015)], followed across 24 years, including diet data from 3 repeated 24-h dietary recalls. We used simultaneous year-stratified linear regression models to examine whether changes in the association between urbanization level and percent of calories from animal-source foods differed by income. Models allowed for variation in associations across the 24 years of urbanization, accounting for within-individual correlation over time and controlling for age, sex, region, physical activity, and caloric intake. Results: In 1991, on average 15% of calories for Chinese adults came from animal source foods and by 2015, this percentage rose to approximately one quarter of total calories. Over the 24 years of follow-up, urbanization and income were each strongly related to percent of calories from animal-source foods with differential association across income levels (p < 0.0001). We also found evidence that this association changed over time (p < 0.0001). Income gradients in animal source food consumption were smallest in the most urban areas in early years with some temporal variation, but over time income gradients narrowed in some later years in low and moderately urbanized areas. However, by 2015 there were few income differences in animal source food consumption across urbanization levels. Conclusions: Throughout 24-years of urbanization, income seemed to buffer the transition from traditional to Western diet. However, the degree to which income buffered these urbanization-related changes depended on the level and history of community urbanization. At later stages of urbanization when Western diet behaviors were more widespread, urban-rural differences in Western diet behaviors varied little by income.